Strategy to Improve the Quality of PJOK Teachers and ISORI Administrators to Improve Sports Education in Tanah Datar - Bafirman, Bafirman; Damrah, Damrah; Zarya, Fiky (STKIP Singkawang, 2024)
Improving the quality of physical, sports, and health education (PJOK) is an important factor in the formation of a healthy and competent young generation. In Tanah Datar Regency, PJOK teachers and the management of the Indonesian Sports Scholars Association (ISORI) play a strategic role in advancing sports education. However, there are obstacles in the implementation of routine training, the use of learning technology, and the limitations of adequate sports facilities. This study aims to analyze efforts to improve the quality of PJOK teachers and ISORI administrators in Tanah Datar Regency, with a focus on education, training, the role of administrators, sports facilities, and their impact on students. Methods This research uses a quantitative approach. Data were obtained through in-depth interviews, direct observations, and documentation studies to get a comprehensive picture of the quality of PJOK education and the role of ISORI administrators. The results show that most PJOK teachers have participated in the training, although the implementation is less structured and the use of technology is still low. ISORI administrators are actively holding trainings and seminars, despite coordination and resource constraints. Most schools have adequate sports facilities, but some still need the government's attention. Improving the quality of teachers and the ISORI program has been proven to increase student motivation, participation, achievement, and encourage a healthy lifestyle. In conclusion, improving the quality of PJOK teachers and ISORI administrators plays an important role in advancing sports education in Tanah Datar Regency. Continuous training, improved coordination, and the provision of adequate facilities are needed to achieve this goal. The impact is not only seen in the improvement of student achievement, but also in the formation of a sustainable healthy lifestyle